2021
DOI: 10.1038/s41467-021-23197-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fate-mapping reveals surface accumulation but not deep organ invasion of pleural and peritoneal cavity macrophages following injury

Abstract: During injury, monocytes are recruited from the circulation to inflamed tissues and differentiate locally into mature macrophages, with prior reports showing that cavity macrophages of the peritoneum and pericardium invade deeply into the respective organs to promote repair. Here we report a dual recombinase-mediated genetic system designed to trace cavity macrophages in vivo by intersectional detection of two characteristic markers. Lineage tracing with this method shows accumulation of cavity macrophages dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
(107 reference statements)
1
24
2
Order By: Relevance
“…Validating this, we utilized the strategy to FACS-purify the populations and assess gene expression ( Figures S3 B–S3D). Fitting with a recent report ( Jin et al., 2021 ), washing the liver prior to digestion enriched the peritoneal macs in the wash fraction, demonstrating these were contaminants on the liver surface rather than being present in the liver tissue itself ( Figure S3 E). While the CITE-seq markers did not discriminate between cluster7 and cluster8, adding CD207 to the panel enabled the non-KCs to be divided into CD207 + and CD207 − macs ( Figure S3 F).…”
Section: Resultssupporting
confidence: 66%
“…Validating this, we utilized the strategy to FACS-purify the populations and assess gene expression ( Figures S3 B–S3D). Fitting with a recent report ( Jin et al., 2021 ), washing the liver prior to digestion enriched the peritoneal macs in the wash fraction, demonstrating these were contaminants on the liver surface rather than being present in the liver tissue itself ( Figure S3 E). While the CITE-seq markers did not discriminate between cluster7 and cluster8, adding CD207 to the panel enabled the non-KCs to be divided into CD207 + and CD207 − macs ( Figure S3 F).…”
Section: Resultssupporting
confidence: 66%
“…Moreover, it’s been suggested serous cavity macrophages may contribute to tissue repair in neighbouring solid organs following injury in mice 174 , 175 . However, elegant intersectional genetics and a combination of injury models have shown that, while pleural GATA6+ macrophages may accumulate on the pleural membrane, they do not migrate deep into the lung parenchyma nor are they essential for fibrogenesis or resolution 176 .…”
Section: Macrophages In Pulmonary Fibrosismentioning
confidence: 99%
“…The immunosuppressive environment of peritoneal and pleural cavities which are frequent sites of cancer progression could be related to these cavity-resident macrophages which express Tim-4 in comparison to tumor-associated macrophages; this expression results in sequestration of cytotoxic T-cells by Tim-4+ cavity-resident macrophages [48]. Interestingly, it is suggested that cavity-resident macrophages do not invade underlying lung, nor do they play a role in tissue repair after injury [49].…”
Section: Immune Cells In Pleural Effusionmentioning
confidence: 99%